Pertanggungjawaban Notaris Werda Atas Akta Yang Pernah Dibuat Dalam Masa Jabatannya - Nala Aprilia Damayanti (Lex Renaissance, 2020)
This research examines how the retired public Notary is responsible for the deeds made during their term of office and how is the legal protection of the retired public Notary. This is a normative legal research with qualitative descriptive analysis. The method used is normative juridical. The result of the research shows that the Notary will still be responsible for the deed made whether the Notary is still in office or has retired. Legal protection for the retired public Notary if there is a problem with the deed that has been made includes the protection of the criminal law as referred to in Article 78 paragraph (1) number 3 of the Criminal Code, as well as in carrying out his position, the Notary must fulfill the obligations as stipulated in Article 16 paragraph (1) of UUJN. Legal protection is provided if the deed has fulfilled the elements of clarity, truth, completeness and legality.